40.9k views
4 votes
Rewrite f(x) = -(x + 3)2 - 1 from vertex form to standard form. (2 points)

Of(x) = -x2 - 6x - 10
Of(x) = x2+ 6x #8
Of(x) = x2 - 6x - 8
Of(x) = x2-8

1 Answer

1 vote

Answer:

f(x) = -x^2 - 6x - 10

Explanation:

Please write the original equation as f(x) = -(x + 3)2 - 1, as "(x + 3)2 is meaningless. We want:

f(x) = -(x + 3)^2 - 1, where " ^ " denotes exponentiation.

Expanding this, we get:

f(x) = -(x^2 + 6x + 9) - 1, or

f(x) = -x^2 - 6x - 9 - 1, or:

f(x) = -x^2 - 6x - 10 This matches the first answer choice.

User Stevemac
by
5.8k points